Use and usefulness of the information systems measurement. A quality approach at the Mexican Northeastern Region - (:unkn) unknown (My University, 2017)
Information technologies have transformed organizations; therefore, identifying their entrepreneurial value has been one of the main concerns for both, managers and researchers. The purpose of this research is to determine the influence of the information systems’ quality on user satisfaction and perceived benefits, and these in turn on the use/usefulness of such technologies in small and medium-sized enterprises of the Mexican northeastern region. Data are collected from 169 questionnaires and analyzed using Partial Least Squares (PLS) and Multi-Group Analysis. The results show that although the users feel satisfied with systems quality, it is not allowing them to make better use and usefulness of information systems. With the Multi-Group Analysis, a significant difference is detected between the relation of perceived benefits and system quality.
Keywords: Information systems, user satisfaction, use/usefulness, PLS, MGA; CIENCIAS SOCIALES [5]